Evaluación de riesgos y mitigación de amenazas a través del cifrado en el sistema activa. - Alvarado Mota, Karla Stephanie (2025)
This case study aims to evaluate the risks associated with unauthorized access and cyber threats in the ACTIVA transactional system, implemented by Western Union in Babahoyo, Ecuador. It focuses on analyzing how the adoption of advanced encryption techniques contributes to mitigating these threats and ensuring the integrity, confidentiality, and availability of data in the point-of-sale profile. The methodology employed included a comprehensive risk analysis based on international standards such as ISO/IEC 27001 and NIST, along with attack scenario simulations to assess the effectiveness of encryption. The results showed a significant reduction in exposure to vulnerabilities due to the use of robust algorithms like AES-256 and complementary techniques such as multi-factor authentication and centralized key management. This study highlights the importance of integrating encryption solutions into transactional environments to strengthen security and increase user trust.